2017
DOI: 10.1093/infdis/jix390
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Oxygen–Free Days in Hematopoietic Cell Transplant Recipients With Respiratory Syncytial Virus

Abstract: Confirmation of RSV infection in the lower respiratory tract provides prognostic information that may help prioritize therapies. Supplemental oxygen-free days as a clinical endpoint may allow smaller sample sizes for trials evaluating RSV antivirals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…9 In contemporary cohorts of HCT recipients with RSV LRTI, the overall mortality ranged from 11%-30%. 3,5,8,10,11 Allo-HCT recipients often have high-risk underlying malignancies and require immunosuppression as compared to auto-HCT recipients. 14 However, we found that mortality was high in all HM patients regardless of HCT status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In contemporary cohorts of HCT recipients with RSV LRTI, the overall mortality ranged from 11%-30%. 3,5,8,10,11 Allo-HCT recipients often have high-risk underlying malignancies and require immunosuppression as compared to auto-HCT recipients. 14 However, we found that mortality was high in all HM patients regardless of HCT status.…”
Section: Discussionmentioning
confidence: 99%
“…Once an RSV diagnosis is confirmed, risk stratification in HM patients is critical given the high cost of therapy with aerosolized ribavirin 7 and high mortality rates after LRTI. 3,5,[8][9][10][11] Prior studies have identified lymphopenia, neutropenia, and RSV detection in lower respiratory samples as important risk factors for mortality after LRTI. 8,[11][12][13] Recognition of individuals at high risk for adverse outcomes could improve the prompt delivery of ribavirin treatment, which may reduce mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum and BAL were routinely tested for Aspergillus with the galactomannan index using the Bio-Rad Platelia Assay (Hercules, CA) [13]. In addition, a multiplex quantitative reverse-transcriptase PCR panel was used to detect 12 respiratory viruses, including influenza A, influenza B, RSV, parainfluenza virus types 1 to 4, adenovirus, human metapneumovirus, coronavirus, rhinovirus, and bocavirus [14]. Invasive fungal infections were defined according to the European Organization for Research and Treatment of Cancer/Mycoses Study Group criteria [15].…”
Section: Definition Of Ipsmentioning
confidence: 99%
“…from 2003 to 2015, no patients with radiographic abnormalities consistent with LRTI but with RSV detected in upper respiratory tract samples only ("possible" RSV LRTI) died, but 28-day mortality was 26% in HCT recipients with probable or proven RSV LRTI [3].…”
mentioning
confidence: 99%